Perusahaan Makanan Segar Sdn Bhd / Mohd Zaki Ramli ... [et al.] - Ramli, Mohd Zaki; Kamsin, Mohd Rizam; Hj Ahmad, Siti Mazuin; Hamzah, Salhamrina; Nasaruddin, Noor Nazreen (Faculty of Information Management, 2003)
Nowadays, the food industries are growth faster according with the development of new technology compared with 10-15 years ago. Due to this, we decided to start our business related with food field. That's why we had chosen to produces noodles as our business activity. About 200 of noodles entrepreneur used automatic machine and some of them are still used half-automatic machine. Most of small entrepreneur noodles only can produces low quantity of noodles especially those are used a regular machine. But the entrepreneur that used sophisticated and latest machine will produce high quantity of noodles.